If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(2x + -5) + -1(2x + -6) + 3 = -4(x + -1) + -1(3x + 5) + 3 Reorder the terms: -1(-5 + 2x) + -1(2x + -6) + 3 = -4(x + -1) + -1(3x + 5) + 3 (-5 * -1 + 2x * -1) + -1(2x + -6) + 3 = -4(x + -1) + -1(3x + 5) + 3 (5 + -2x) + -1(2x + -6) + 3 = -4(x + -1) + -1(3x + 5) + 3 Reorder the terms: 5 + -2x + -1(-6 + 2x) + 3 = -4(x + -1) + -1(3x + 5) + 3 5 + -2x + (-6 * -1 + 2x * -1) + 3 = -4(x + -1) + -1(3x + 5) + 3 5 + -2x + (6 + -2x) + 3 = -4(x + -1) + -1(3x + 5) + 3 Reorder the terms: 5 + 6 + 3 + -2x + -2x = -4(x + -1) + -1(3x + 5) + 3 Combine like terms: 5 + 6 = 11 11 + 3 + -2x + -2x = -4(x + -1) + -1(3x + 5) + 3 Combine like terms: 11 + 3 = 14 14 + -2x + -2x = -4(x + -1) + -1(3x + 5) + 3 Combine like terms: -2x + -2x = -4x 14 + -4x = -4(x + -1) + -1(3x + 5) + 3 Reorder the terms: 14 + -4x = -4(-1 + x) + -1(3x + 5) + 3 14 + -4x = (-1 * -4 + x * -4) + -1(3x + 5) + 3 14 + -4x = (4 + -4x) + -1(3x + 5) + 3 Reorder the terms: 14 + -4x = 4 + -4x + -1(5 + 3x) + 3 14 + -4x = 4 + -4x + (5 * -1 + 3x * -1) + 3 14 + -4x = 4 + -4x + (-5 + -3x) + 3 Reorder the terms: 14 + -4x = 4 + -5 + 3 + -4x + -3x Combine like terms: 4 + -5 = -1 14 + -4x = -1 + 3 + -4x + -3x Combine like terms: -1 + 3 = 2 14 + -4x = 2 + -4x + -3x Combine like terms: -4x + -3x = -7x 14 + -4x = 2 + -7x Solving 14 + -4x = 2 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 14 + -4x + 7x = 2 + -7x + 7x Combine like terms: -4x + 7x = 3x 14 + 3x = 2 + -7x + 7x Combine like terms: -7x + 7x = 0 14 + 3x = 2 + 0 14 + 3x = 2 Add '-14' to each side of the equation. 14 + -14 + 3x = 2 + -14 Combine like terms: 14 + -14 = 0 0 + 3x = 2 + -14 3x = 2 + -14 Combine like terms: 2 + -14 = -12 3x = -12 Divide each side by '3'. x = -4 Simplifying x = -4
| 6p+4p+.75+3p= | | -73+8x=71 | | 3(m-z)+5(2m-z)=0 | | 7p^2=-18p-8 | | 12x+15(312-x)=13*312 | | 33x^2+39x=0 | | -86=-2(3n+1)-6n | | -83=10x+97 | | 7y+(5y+5)= | | 8x+5-6(x+1)=7x+3 | | 2y+3(y-9)=-3(3y-18)-y | | -7(1+3x)=161 | | 1=5p-2-2 | | (c)8-10=3c+5 | | 5-[2(-4)-1]=10-x | | 2x+20=46 | | -212=-2-6(5v-2) | | 3(4-7)=-21+12z | | 5-[(-4)-1]=10-x | | x^3+2x^3=72 | | v^2-16-6v=0 | | -4y-1(5y+6)=-7y+3 | | -2(8n+1)-4(n+5)=-2 | | 2/3(3x-9)=1/4(4x-12) | | 13r-8-12= | | 10x+5+8=12x-3x+8 | | 9=4x-x | | 6(1-2m)-4(m+1)=50 | | v=x(19-2x)(8.5-2x) | | 600=4x+8x | | 600=4x*8x | | -143=-11*x |